Penerapan Akupresure LI4 untuk Mencegah Kala 1 Lama pada Primipara - Debi Dahliyani; Siti Mutoharoh (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
Background: One of the causes of maternal mortality is prolonged labor. It is a labor process lasting more than 24 hours. Most of long parturition shows lengthening in stage 1. LI-4 acupressure is a very simple procedure and easy to do. It has minimal side effects and is used for natural induction of labor. Objective: Applying LI-4 acupressure to prevent a long stage 1 of primipharous. Method: This study is an analytical descriptive with a case study approach. The participants were 5 primipharous mothers who had been in stage 1 of active phase. The instrument was a patograph. Result: After having application LI-4 acupressure, there was an increase of contractions of all participants – from 3 times became 4 - 5 times, and from moderate became more adequate of primipharous mothers in stage 1 of active phase, so that it can prevent a long period in primipharou. Conclusion: The application of LI-4 acupressure can effectively prevent a long stage 1 of primipharous.